Evaluation of 90nm 6T-SRAM as Physical Unclonable Function for secure key generation in wireless sensor nodes - Selimis, Georgios; Konijnenburg, Mario; Ashouei, Maryam; Huisken, Jos; de Groot, Harmke; van der Leest, Vincent; Schrijen, Geert-Jan; van Hulst, Marten; Tuyls, Pim (2011 IEEE International Symposium of Circuits and Systems (ISCAS), 2011)
Due to the unattended nature of WSN (Wireless Sensor Network) deployment, each sensor can be subject to physical capture, cloning and unauthorized device alteration. In this paper, we use the embedded SRAM, often available on a wireless sensor node, for secure data (cryptographic keys, IDs) generation which is more resistant to physical attacks. We evaluate the physical phenomenon that the initial state of a 6T-SRAM cell is highly dependent on the process variations, which enables us to use the standard SRAM circuit, as a Physical Unclonable Function (PUF). Important requirements to serve as a PUF are that the start-up values of an SRAM circuit are uniquely determined, unpredictable and similar each time the circuit is turned on. We present the evaluation results of the internal SRAM memories of low power ICs as PUFs and the statistical analysis of the results. The experimental results prove that the low power 90nm commercial 6T-SRAMs are very useful as a PUF. As far as we know, this is the first work that provides an extensive evaluation of 6T-SRAM-based PUF, at different environmental, electrical, and ageing conditions to representing the typical operating conditions of a WSN.